2016
DOI: 10.3389/fnhum.2016.00197
|View full text |Cite
|
Sign up to set email alerts
|

Pantomime-Grasping: Advance Knowledge of Haptic Feedback Availability Supports an Absolute Visuo-Haptic Calibration

Abstract: An emerging issue in movement neurosciences is whether haptic feedback influences the nature of the information supporting a simulated grasping response (i.e., pantomime-grasping). In particular, recent work by our group contrasted pantomime-grasping responses performed with (i.e., PH+ trials) and without (i.e., PH− trials) terminal haptic feedback in separate blocks of trials. Results showed that PH− trials were mediated via relative visual information. In contrast, PH+ trials showed evidence of an absolute v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Our findings are consistent with those from a previous investigation that tested memory-guided pantomime grasps directed at the remembered location of a previewed object with and without haptic feedback (Davarpanah Jazi and Heath, 2016). In the haptic-feedback condition, after the participants completed their pantomime grasp, the previewed target was placed between their thumb and index finger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with those from a previous investigation that tested memory-guided pantomime grasps directed at the remembered location of a previewed object with and without haptic feedback (Davarpanah Jazi and Heath, 2016). In the haptic-feedback condition, after the participants completed their pantomime grasp, the previewed target was placed between their thumb and index finger.…”
Section: Discussionsupporting
confidence: 91%
“…The haptic and no-haptic conditions were blocked separately or randomly interleaved and left uncued. The authors found that grip aperture violated Weber's law, which has been adopted as index of absolute vs. relative coding of target size (e.g., Ganel et al, 2008;Holmes et al, 2013;Manzone et al, 2017;Ozana and Ganel, 2018b; but see Foster and Franz, 2013;Löwenkamp et al, 2015), for the haptic conditions only when blocked separately (Davarpanah Jazi and Heath, 2016). It is unknown, however, whether their findings are due to a cued expectation for haptic feedback or to visuo-haptic calibration, because the authors did not test a cued variant of their randomized haptic schedule.…”
Section: Discussionmentioning
confidence: 99%
“…In grasping, the JND is measured as the within-participant variability of the maximal finger aperture during the reach-tograsp movement and it remains invariant with object size, in violation of Weber's law (Ganel et al, 2008). Several experimentally confirmed hypotheses have been suggested for explaining this phenomenon (Smeets and Brenner, 2008;Jazi et al, 2015;Löwenkamp et al, 2015;Utz et al, 2015;Jazi and Heath, 2016).…”
mentioning
confidence: 99%
“…It is therefore not surprising that withholding information about the contact points or how they can be reached can influence the whole grasping movement. This has been demonstrated for haptic information (Cuijpers et al 2008;Schenk 2012;Davarpanah Jazi and Heath 2016) as well as for visual information Bozzacchi et al 2018). We therefore designed our set-up in a manner that provided our participants with both visual and haptic feedback near the point of contact, despite restricting the visual feedback to the last part of the digits' trajectories.…”
Section: Discussionmentioning
confidence: 99%